Risk management against the mindset of PGSD students in entrepreneurship - Maharani Putri, Dian; Zamhari, Ahmad; Afriza, Agnes; Maharani, Ira; Afriyansya, Nando (ARKA INSTITUTE, 2024)
This study aims to find out how Risk Management Against the Mindset of PGSD Students in Entrepreneurship. Using the Quantitative Approach Method by calculating student data about the risks to the mindset of every PGSD student at PGRI Palembang University. The sample used was 40 first grade PGSD students. By conducting surveys, distributing questionnaires and determining the scale of the entrepreneurial mindset then analyzing data for each PGSD student in entrepreneurship. The results of this study are to prove that the risk mindset of PGSD students in entrepreneurship can develop the businesses they develop through their mindset, and by taking the questionnaire researchers can find out how much risk management mindset they face.